2018
DOI: 10.1002/cctc.201801585
|View full text |Cite
|
Sign up to set email alerts
|

Ni/LnOx Catalysts (Ln=La, Ce or Pr) for CO2 Methanation

Abstract: The effect of the LnOx support has been studied for Ni‐based CO2 methanation catalysts. 10 wt.% nickel catalysts with LaOx, CeO2 and PrOx supports have been prepared, characterized by N2 adsorption, XRD, XRF, TG‐MS (N2‐TPD and H2‐TPR) and XPS, and have been tested for CO2 methanation. The catalytic activity follows the trend Ni/CeO2>Ni/PrOx≫Ni/LaOx, all catalysts being very selective towards CH4 formation. The activity depends both on the nature of the catalytic active sites and on the stability of the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 61 publications
(118 reference statements)
2
30
1
Order By: Relevance
“…Two additional thermal processes should also be taken into consideration; decomposition of the La(OH) 3 and LaO 2 CO 3 phases that take place at around 350 C and 750 C, respectively, as carbonates are more stable than the hydroxides. 83 The nature and structure of the carbonaceous species deposited on to the spent catalysts was also investigated using Raman spectroscopy and as can be observed in Fig. 10a and b, both catalysts show two well resolved bands around 1340 cm À1 and 1580 cm À1 .…”
Section: Catalyst Stability and Carbon Deposition Studiesmentioning
confidence: 97%
“…Two additional thermal processes should also be taken into consideration; decomposition of the La(OH) 3 and LaO 2 CO 3 phases that take place at around 350 C and 750 C, respectively, as carbonates are more stable than the hydroxides. 83 The nature and structure of the carbonaceous species deposited on to the spent catalysts was also investigated using Raman spectroscopy and as can be observed in Fig. 10a and b, both catalysts show two well resolved bands around 1340 cm À1 and 1580 cm À1 .…”
Section: Catalyst Stability and Carbon Deposition Studiesmentioning
confidence: 97%
“…The adsorbed hydrogen atoms on the Pd surface were then proposed to spillover to Mg carbonates, hydrogenating the CO 2 -adsorbed phases and forming the CH 4 final product. This bifunctional character of CO 2 methanation reaction that requires the presence of a catalyst componentent capable of activating the CO 2 (Supporting Material: even the commonly considered "inert" Al 2 O 3 acts in this way; support doping is often used for further enhancing this role), and a metallic component typically active in H 2 dissociation has been well established in the literature [60][61][62].…”
Section: Magnesium (Mg)mentioning
confidence: 98%
“…Cárdenas-Arenas and co-workers, examining the CO 2 methanation mechanism over Ni/CeO 2 and Ni/Al 2 O 3 by isotopic and in situ DRIFTS, proposed the synergistic cooperation of Ni-CeO 2 interface and Ni 0 phase responsible for the activation of CO 2 and H 2 enhanced the methanation activity and selectivity over Ni/CeO 2 [18]. Alcalde-Santiago et al linked the highest activity of Ni/CeO 2 (relative to Ni/PrO x and Ni/LaO x ) to the MSI that generated the highest population of active sites for CO 2 /H 2 activation and the lowest stability of surface CO 2 and H 2 O species [23]. A structure sensitivity was reported that the turnover frequency (TOF) increased with an increase of Ni particle size in the reaction over Ni/CeO 2 [24].…”
Section: Introductionmentioning
confidence: 99%